Sunset - Hunter, Erin. (New York : HarperCollins, 2007)
Amidst ongoing strife within and between the Clans of warrior cats, Brambleclaw is tempted by the dark plans of his father and brother, and the meaning of Leafpool's ominous visions becomes clear.
5.1
5-8
Keywords: Cats -- Juvenile fiction; Prophecies -- Juvenile fiction; Revenge -- Juvenile fiction; Cats -- Fiction; Prophecies -- Fiction; Revenge -- Fiction; Fantasy; Cats -- Fiction; Prophecies -- Fiction; Revenge -- Fiction; Fantasy fiction; Fantasy fiction